The impact of the use of collaborative style in the development of skill transmitter in volleyball for middle school students - Abd, Taraq; Gmah, Kausar (Journal of Physical Education, 2014)
Turning the researcher to find out how much the effectiveness of the use of style Cooperative and its impact on the learning skill transmission volleyball and development, Vtmahort problem about multiple learning styles and use them to learn sports in the middle stage but it remains the best method that suits each stage and the game in line with the possibilities and the decisions of the educated and the investment of time and effort to get to achieve the desired goals, where I took the researcher undertook a study skill transmission from the bottom volleyball on the first-grade students Mediterranean, where it was to identify two groups represent one control group and the other experimental and each group consisted of 12 students with two units elite educational week distributor (6) weeks has been a parity of the research sample and then exploratory experiment and after the tests and the application of the tribal experience and finally the main post-test and then extract the results that have placed the conclusions and recommendations which have been developed.